Current and emerging pharmacotherapy for respiratory syncytial virus (RSV) infection in infants. (13th April 2023) - Principi, Nicola; Autore, Giovanni; Perrone, Serafina; Esposito, Susanna
ABSTRACT: Introduction: Respiratory syncytial virus (RSV) is a common respiratory virus with a huge impact on patients, the healthcare system, and society worldwide. Very few effective chances of prevention and treatment of RSV infection are available. Areas covered: In this paper, knowledge on RSV characteristics and current stage of development of new pharmacological measures against this virus are discussed. Expert opinion: In recent years, the structure of RSV was explored in depth and several pharmacologic measures potentially effective for prevention and treatment of RSV infection and disease were identified. These new measures have the aim to overcome the limitations of palivizumab and ribavirin. Strategies to protect infants through immunization of pregnant women and/or the use of more effective monoclonal antibodies were developed. At the same time, it was defined which vaccines could be administered to unprimed infants to avoid the risk of enhanced respiratory disease and which vaccines could be effective in older patients and in subjects with reduced immune system efficiency. Finally, a great number of new antiviral drugs targeting the RSV proteins that allow RSV entering host cells or regulate virus replication were produced. Although further studies are needed, some preparations seem effective and safe, making the future of RSV infection prevention and treatment less gloomy.